Análise da evolução costeira do litoral setentrional do Estado do Rio Grande do Norte, região sob influência da indústria petrolífera - Souto, Michael Vandesteen Silva (2009)
The northern coast of Rio Grande do Norte State is characterized by strong changes in coastal morphology, caused by various geological and climatic factors. In this region are installed the main socio-economic activities of the State, highlighting the oil industry, which exerts much of its activities in the coastal area studied. Erosion is a constant problem in this region because it affects the entire local populace to the destruction of houses and trade, rendering tourism, affecting the livelihood activities and industrial activities. The greatest risk is related to environmental damage that can be caused by the oil spill in this region. To understand what determines the changes in coastal morphology this Doctoral Thesis is proposed to identify the factors at local, regional and even global corroborate coastal dynamics to this coast in question. For this study, used several different products and tools for interpreting the conditions of the erosive effect that dominates the whole northern coast of the State, in an attempt to quantify and describe the causes and effects that affect the entire coastal zone monitored. The development of activities is built into the projects Rede 05 PETROMAR (CTPETRO-FINEP/PETROBRAS/CNPq), PETRORISCO, HIDROSEMA, PETROMAR e Rede 05/04 POTMAR (FNDCT/CTPETROFINEP/ CNPq), in the activities of multidisciplinary and inter-features in issues involving environmental monitoring and oil activity